Integration of Informal Waste Segregation (Scavenging) for Efficient Waste Management System Iin Anambra State, Nigeria - Okonkwo , Augustina U (African Journal of Education,Science and Technology (AJEST), 2017)
Studies have shown that informal waste segregation otherwise known as scavenging has contributed to the economic development of many countries in the world. This study explores the costs and benefits of scavenging in two cities of Anambra State of Nigeria with a view to determine its contribution to the economy and efficient waste management. The studies were carried out through interviews and structured questionnaire. The information sought were on socio-economic characteristics of scavengers, income, risks involved, benefits, scavenged materials, challenges etc. Two hypotheses, each, were postulated for the study carried out in Awka and Nnewi based on if there are significant costs and benefits of scavenging to the environment. The validity of the hypotheses was tested with chi-square and the results showed significant costs as well as benefits of scavenging activities to the environment. This paper is recommending a formalization of informal waste segregation and building it into the operations of the Waste Management Authority. Thus reducing the costs and risks and reaping the benefits to the enhancement of the economy, provision of legal means of livelihood and efficient waste management system.